Individual predisposition, household clustering and risk factors for human infection with Ascaris lumbricoides: new epidemiological insights. - Martin Walker; Andrew Hall; María-Gloria Basáñez (Public Library of Science (PLoS), 2011)
Much of our current understanding of the epidemiology of Ascaris lumbricoides infections in humans has been acquired by analyzing worm count data. These data are collected by treating infected individuals with anthelmintics so that worms are expelled intact from the gastrointestinal tract. Analysis of such data established that individuals are predisposed to infection with few or many worms and members of the same household tend to harbor similar numbers of worms. These effects, known respectively as individual predisposition and household clustering, are considered characteristic of the epidemiology of ascariasis. The mechanisms behind these phenomena, however, remain unclear. In particular, the impact of heterogeneous individual exposures to infectious stages has not been thoroughly explored.Bayesian methods were used to fit a three-level hierarchical statistical model to A. lumbricoides worm counts derived from a three-round chemo-expulsion study carried out in Dhaka, Bangladesh. The effects of individual predisposition, household clustering and household covariates of the numbers of worms per host (worm burden) were considered simultaneously. Individual predisposition was found to be of limited epidemiological significance once household clustering had been accounted for. The degree of intra-household variability among worm burdens was found to be reduced by approximately 58% when household covariates were included in the model. Covariates relating to decreased affluence and quality of housing construction were associated with a statistically significant increase in worm burden.Heterogeneities in the exposure of individuals to infectious eggs have an important role in the epidemiology of A. lumbricoides infection. The household covariates identified as being associated with worm burden provide valuable insights into the source of these heterogeneities although above all emphasize and reiterate that infection with A. lumbricoides is inextricably associated with acute poverty.